Investigations into the distribution and diversity of shallow eroded areas on steep grasslands in Tyrol (Austria) - Wiegand, Christoph; Geitner, Clemens (ERDKUNDE, 2013)
On many slopes in the Alps one can find small shallow eroded areas. In some areas an increase in such erosion forms has been documented and related to changes in land use in recent decades. Possible effects of changes in climatic conditions must also be taken into account in this context. The size of the eroded areas discussed in this paper ranges from 2 m2 to 200 m2 and their depth rarely exceeds a few decimetres. They also present clearly delineated scarps. The material transfer occurs in the unconsolidated material and may reach into the bedrock in individual cases. The eroded areas can occur as shallow landslides or as the result of erosion by snow movement. Key factors in these processes are the composition and layering of the unconsolidated material, the climatic framework, topography, land cover and land use. This paper discusses shallow eroded areas in Tyrol (Austria). Initially the distribution pattern of affected areas within Tyrol was studied on the basis of expert interviews and after analysing aerial photographs. Then 161 individual eroded areas in eight study areas were captured using a standardized documentation sheet and compared in terms of site and shape characteristics. From this it transpired that by far the regions with most eroded areas are found in the northern, limestone dominated regions of Tyrol. Moreover, the results indicate that the majority of all recorded shallow eroded areas seemed to be caused by snow movement what can be deduced from certain location parameters (e.g. aspect, inclination), shape and shallow depth of erosion. The comparison with results from other studies also suggests this conclusion. Nevertheless in individual cases there are uncertainties in concluding on the forming processes based on the mentioned properties of the shallow eroded areas.